Get expert insights and reliable answers to your questions on IDNLearn.com. Whether your question is simple or complex, our community is here to provide detailed and trustworthy answers quickly and effectively.
Answer:
Step-by-step explanation:
This will be a sum of two geometric sequences, one for distance falling and one for distance rising. The sum of a geometric sequence is expressed as s=a(1-r^n)/(1-r) where a=initial term, r=common ratio, and n= number of terms.
For the falling distance we have
f=3(1-.5^n)/(1-.5) as n goes to infinity it is just f=3/(.5)
For rising distance we have
r=1.5(1-.5^n)/(1-.5) and again as n goes to infinity it is r=1.5/(.5)
So the total distance travelled is
d=f+r
d=3/0.5+1.5/0.5
d=6+3
d=9 meters